125 Treatment outcome in lupus nephritis patients treated with mycophenolate mofetil: from a real-world clinical practice. (April 2019) - Jung, Seung Min; Ahn, Sung Soo; Lee, Sang-Won; Song, Jason Jungsik; Park, Yong-Beom
Abstract : Background: Systemic lupus erythematosus (SLE) is autoimmune disorder often characterized by the development of glomerulonephritis. The use of mycophenolate mofetil (MMF) is highlighted as induction and maintenance therapy in lupus nephritis. We evaluated the treatment outcome of MMF in lupus nephritis patients from a real clinical practice. Methods: Patients with biopsy proven lupus nephritis (class III, IV, and V) between November 2005 and August 2017 in Severance Hospital were extracted, and those patients who were treated with MMF at least 3 months were included in this study. The remission rate of lupus nephritis and risk factors for failure of remission were evaluated using Kaplan-Meier analysis and Cox proportional hazards model. Results: Of 116 patients included in this study, 89 (76.7%) patients achieved remission of lupus nephritis after treatment with MMF. The median time to remission was 4.2 months (interquartile range 0.9 9.1). Normal complement level, negative result of anti-dsDNA antibody, and nephrotic range proteinuria were risk factors for remission failure in univariate analysis (p=0.017, 0.001, and 0.007, respectively). Nephrotic range proteinuria and negative result of anti-dsDNA antibody are independently associated with remission failure in multivariate analysis (OR 3.19, p=0.004 and OR 1.62, p=0.028, respectively). Conclusions: Patients with lupus nephritis showed a favourable clinical outcome after MMF treatment. However, additional therapy would be required in patients with nephrotic-range proteinuria and without anti-dsDNA antibody. Funding Source(s): None